2006
DOI: 10.1128/aac.00571-06
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Activities of DA-7157 and DA-7218 against Mycobacterium tuberculosis and Nocardia brasiliensis

Abstract: The in vitro activities of DA-7157, a novel oxazolidinone, against clinical isolates of Nocardia brasiliensis and Mycobacterium tuberculosis were determined. Equal MIC 50 s and MIC 90 s (0.25 and 0.5 g/ml, respectively) were found for susceptible and multidrug-resistant isolates of M. tuberculosis. The N. brasiliensis isolates showed an MIC 90 of 1 g/ml and an MIC 50 of 1 g/ml. The DA-7157 prodrug, DA-7218, exhibited similar MICs for M. tuberculosis but fivefold-higher MICs for N. brasiliensis.Oxazolidinones a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
40
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(41 citation statements)
references
References 8 publications
0
40
0
1
Order By: Relevance
“…Newer oxazolidinones such as DA-7867, DA-7157, RBx 7644, and RBx 8700 have better in vitro activity against M. tuberculosis than linezolid (33,34) and might be better drugs for TB treatment than linezolid. Our results suggest that further studies are warranted to evaluate the effectiveness of oxazolidinones as anti-TB drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Newer oxazolidinones such as DA-7867, DA-7157, RBx 7644, and RBx 8700 have better in vitro activity against M. tuberculosis than linezolid (33,34) and might be better drugs for TB treatment than linezolid. Our results suggest that further studies are warranted to evaluate the effectiveness of oxazolidinones as anti-TB drugs.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro it is active against M tuberculosis and might have less mitochondrial toxicity than linezolid, but tedizolid has not been tested in patients with tuberculosis or given for prolonged periods. 347,348 Sutezolid is an investigational oxazolidinone in phase 2 testing for tuberculosis (table 8). Preclinical data suggest it could be more efficacious than linezolid, but a high incidence (14%) of liver enzyme elevations in an early bactericidal activity study was reported.…”
Section: Oxazolidinonesmentioning
confidence: 99%
“…Tedizolid phosphate ( 3 ; previously torezolid phosphate, TR‐701, DA‐7218) is the inactive prodrug of tedizolid ( 4 ; previously torezolid, TR‐700, DA‐7157, which was discovered by Dong‐A Pharmaceuticals, and developed by Trius Therapeutics and Cubist Pharmaceuticals) 37, 38. After two successful phase III trials, tedizolid was approved by the Food and Drug Administration (FDA) in June 2014 under the trade name Sivextro for the treatment of MRSA skin infections (Figure 5).…”
Section: Protein Synthesis Inhibitorsmentioning
confidence: 99%